Effects of institutions on ecological attitudes and behaviour of consumers in a developing Asian country: the case of the Philippines. (30th April 2015) - Martinez, Carmelita P.; Castaneda, Marigold G.; Marte, Rodilina B.; Roxas, Banjo
Abstract: This study examines the effects of institutions emanating from the social environment on ecologically sustainable consumer behaviour in a developing country context. Drawing on the behavioural perspective model of consumer choice and institutional theory, this study argues that the regulative, normative and cognitive dimensions of the institutional environment play critical roles in shaping the pro‐environmental attitudes called eco‐attitudes of consumers. In turn, eco‐attitudes positively influence the eco‐behaviour of consumers. The structural equation modelling of data from a survey of 1045 consumers from the Philippines shows the significant and positive effects of the regulatory, normative and cognitive dimensions of the institutional environment on the eco‐attitudes of consumers, which in turn have strong positive influence on eco‐behaviour. The findings about the partial mediating role of eco‐attitudes offer a more nuanced explanation on how institutions explain the eco‐behaviour of consumers which is a topic that is less understood especially in a developing country context. The study highlights the theoretical, methodological, policy and future research implications of the findings.